Efecto del software MindMaster en el diseño del diagrama de Ishikawa con estudiantes de Ciencias Sociales de la FCEH – UNAP Iquitos – 2024 - Garcia Romero, Norma Jesus (2025)
The objective was to determine the effect of MindMaster software in the design of the Ishikawa diagram with students of Social Sciences, developed through an experimental methodology of quasi-experimental type with two groups, one experimental and one control, where we sought to find the effect of MindMaster software in the design of the Ishikawa diagram, variables that were studied in a population of 186 students of the Social Sciences career of the Faculty of Education Sciences and Humanities - UNAP, being the non-probabilistic intentional sample where all the students of 4th level were chosen, which were 46 students to whom the technique of the survey and the direct observation were applied, applying a questionnaire and a data collection sheet, arriving at the following results: with non-parametric statistical test of U-Mann Whitney, it was observed that the values of bilateral significance were greater than 5%, this shows that the results of the students in the experimental and control groups at the beginning of the experiment are equal in relation to the design of the Ishikawa diagram, which indicates that the groups are equivalent in the pre-test and then in the result of the non-parametric statistical test of U-Mann Whitney, it could be seen that the values of the bilateral significance were less than 5%,this shows that the results of the students in the experimental and control groups at the end of the experiment are different with respect to the design of the Ishikawa diagram, so it is affirmed that the results were significant; reaching the conclusion that the application of MindMaster software improves the design of the Ishikawa diagram in students of Social Sciences of the FCEH - UNAP.